2015
DOI: 10.1007/s12035-015-9283-2
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin Cleavage in In Vitro Brain Ischemia Decreases GABAA Receptor Clustering and Contributes to Neuronal Death

Abstract: GABA (γ-aminobutyric acid) is the major inhibitory neurotransmitter in the central nervous system, and changes in GABAergic neurotransmission modulate the activity of neuronal networks. Gephyrin is a scaffold protein responsible for the traffic and synaptic anchoring of GABAA receptors (GABAAR); therefore, changes in gephyrin expression and oligomerization may affect the activity of GABAergic synapses. In this work, we investigated the changes in gephyrin protein levels during brain ischemia and in excitotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 55 publications
7
48
0
Order By: Relevance
“…Most studies that have been published so far reported no alteration in synaptophysin expression level under ischemic and excitotoxic conditions. This was the case in cultured hippocampal neurons subjected to transient OGD and in the ischemic region induced by transient MCAO (Costa et al, 2015;Curcio et al, 2015;Lobo et al, 2011;Mele et al, 2014). Similar results were obtained in cultured hippocampal neurons subjected to excitotoxic stimulation with glutamate Gomes et al, 2011) and following intrahippocampal injection of kainate .…”
Section: Calpain-mediated Cleavage Of Synaptophysinsupporting
confidence: 77%
See 3 more Smart Citations
“…Most studies that have been published so far reported no alteration in synaptophysin expression level under ischemic and excitotoxic conditions. This was the case in cultured hippocampal neurons subjected to transient OGD and in the ischemic region induced by transient MCAO (Costa et al, 2015;Curcio et al, 2015;Lobo et al, 2011;Mele et al, 2014). Similar results were obtained in cultured hippocampal neurons subjected to excitotoxic stimulation with glutamate Gomes et al, 2011) and following intrahippocampal injection of kainate .…”
Section: Calpain-mediated Cleavage Of Synaptophysinsupporting
confidence: 77%
“…A calpain-mediated downregulation of GABAAR subunits (α1, β3, α2 and γ2) and gephyrin was observed in cultured hippocampal neurons subjected transiently to OGD (Figure 6) (Mele et al, 2014). Moreover, it was shown that calpains cleave gephyrin under excitotoxic conditions, both in cultured hippocampal neurons and in vivo, giving rise to a stable cleavage product with ~47 kDa (Costa et al, 2015). Indeed, chemical inhibition of calpain abrogated the cleavage of gephyrin observed in hippocampal neurons subjected to OGD or to excitotoxic injury.…”
Section: 2effects Of Calpain Activity At Gabaergic Postsynaptic Simentioning
confidence: 93%
See 2 more Smart Citations
“…Downregulation of gephyrin expression by gene targeting or gene silencing leads to the rapid disappearance of postsynaptic GABA A R clustering, and loss of inhibitory postsynaptic currents (IPSCs) [22][23][24] . Thus, gephyrin promotes the stabilization of GABA A Rs at postsynaptic sites and serves as an important regulator of GABAergic neurotransmission [25][26][27][28] . However, the role of gephyrin in cocaine addiction has not been studied.…”
Section: Introductionmentioning
confidence: 99%